A study of Traditional Games “Engklek” in Mathematics for Elementary School - Asrial, Asrial; Syahrial, Syahrial; Maison, Maison; Kurniawan, Dwi Agus; Perdana, Rahmat (Jurnal Ilmu Pendidikan, 2020)
This study aims to determine whether elementary school teachers know the traditional game "Engklek" can be integrated into learning. Because, by following the 2013 curriculum implemented by the government must integrate the values that are around into learning. The research method used is a mixed method with a sequential explanatory model, in which the number of samples in this study were 34 respondents who came from elementary school teachers in Batanghari through observation sheets and interviews conducted with respondents. The results in this study the teacher has a good category of teacher knowledge of traditional games, will remain, the teachers do not know that traditional games can be integrated into learning, even though by applying them into learning in addition to educating students, it can also help preserve their culture.